From lab novice to research enthusiast: my transformative internship at UiTM / Nurul Syahmin Ab Aziz - Ab Aziz, Nurul Syahmin (Faculty of Pharmacy, 2024)
During my final year in the BSc Biomedical Sciences program at the University of Warwick, United Kingdom, I had the opportunity to do an internship at the Group for Affinity, Safety and Efficacy Studies (OASES) research initiative group laboratory, Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam. Under the guidance of Dr. Aisyah Hasyila Jahidin and Prof. Dr. Mizaton Hazizul Hasan, I explored the impact of TRPML1 inhibition using ML-SI1 on triple-negative breast cancer under serum-starved conditions. This internship, generously funded by the Warwick Turing Scheme and running from July 15 to September 30, 2024, provided invaluable hands-on experience that will shape my future career.